Pengaruh Inventarisasi Aset, Legal Audit Dan Struktur Birokrasi Terhadap Optimalisasi Pengelolaan Barang Milik Daerah Pada Pemerintah Kabupaten Aceh Besar - Ilham Perdana Putra; Intan Rizkia Chudri; Fitri Yunina (CV. ITTC INDONESIA, 2025)
The problem addressed in this study is the suboptimal management of Regional Government Assets (Barang Milik Daerah/BMD) in Aceh Besar Regency, which is marked by discrepancies between physical and administrative asset data, weak legal safeguards for assets, and a bureaucratic structure that has yet to effectively support asset management. This study aims to analyze the effect of asset inventory, legal audit, and bureaucratic structure simultaneously and partially on the optimization of BMD management in the Government of Aceh Besar Regency. The population in this study consists of government officials involved in BMD management across all Regional Work Units (SKPD) in Aceh Besar Regency, totaling 66 officials. Each SKPD is represented by two selected samples: the Head of the Finance Subdivision and the BMD Manager. Sampling was conducted using a non-probability saturated sampling technique, in which all population members are used as samples—also known as a census. The results show that asset inventory, legal audit, and bureaucratic structure simultaneously influence the optimization of BMD management in SKPDs of Aceh Besar Regency, with an R value of 0.689. Asset inventory has a positive effect on the optimization of BMD management, with a regression coefficient of 0.241. Legal audit also has a positive effect, with a regression coefficient of 0.240. Meanwhile, bureaucratic structure has a positive effect with a regression coefficient of 0.266.